Current Development of Silver Nanoparticle Preparation, Investigation, and Application in the Field of Medicine. (19th May 2015) - Murphy, Maxwell; Ting, Kang; Zhang, Xinli; Soo, Chia; Zheng, Zhong
Abstract : The invited review covers different research areas of silver nanoparticles (AgNPs), including the synthesis strategies of AgNPs, antimicrobial and anti-inflammatory properties of AgNPs, osteoconductive and osteoinductive activities of AgNP-based materials, and potential toxicity of AgNPs. The potential mechanisms of AgNP's biological efficacy as well as its potential toxicity are discussed as well. In addition, the current development of AgNP applications, especially in the area of therapeutics, is also summarized.